Perbudakan dalam Perspektif M. Quraish Shihab; Telaah atas Term Perbudakan dalam Tafsir Al-Mishbah - Ihya' Ulumudin (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
Slavery is one of the terms written in the Qur'an. Slavery in the discussion of the Qur'an is included in the context of human liberation from oppression. That is, the Qur'an is here to liberate humans from oppression. The portrait presented by the Qur'an is slavery when the Qur'an was revealed to Rasulullah SAW. This study aims to explore the terms of slavery (رقاب/رقبة) contained in the Qur'an. The search was carried out on the book of interpretation by M. Quraish Shihab, Tafsir al-Mishbah. The author uses a descriptive-analytical method with a historical and philosophical approach in this study. This study found that the abolition of slavery written in the Qur'an was not completed. That is, there is a new model of slavery in the period after the Prophet's prophethood and even today. Modern slavery, in the view of M. Quraish Shihab, becomes wider than slavery in the past context. Modern slavery can take the form of slavery in political, economic, social and so on.